2022
DOI: 10.1029/2021gl097269
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Dynamics of Spontaneous Imbibition in Porous Media: From Pore Scale to Darcy Scale

Abstract: In porous media research, spontaneous imbibition is capillary-driven invasion of the wetting phase displacing the nonwetting phase, which is governed by the interplay of capillary force and viscous force. As a typical two-phase flow process, it plays an important role in numerous practical problems such as oil production from fractured reservoirs (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…As such, their validity for viscoelastic fluids is questionable. In a recent work, Qin et al 28 have demonstrated that, for Newtonian fluids, the closed conduits in heterogeneous porous materials such as sandstone can affect the wetting dynamics of the displacing liquid. It can be argued that the situation becomes much more complicated for viscoelastic fluids because, for such fluids, the open conduits are regions of high elastic stresses, while the closed conduits are regions of low shear stress.…”
Section: Two-phase Imbibition Model For Viscoelastic Liquidsmentioning
confidence: 99%
“…As such, their validity for viscoelastic fluids is questionable. In a recent work, Qin et al 28 have demonstrated that, for Newtonian fluids, the closed conduits in heterogeneous porous materials such as sandstone can affect the wetting dynamics of the displacing liquid. It can be argued that the situation becomes much more complicated for viscoelastic fluids because, for such fluids, the open conduits are regions of high elastic stresses, while the closed conduits are regions of low shear stress.…”
Section: Two-phase Imbibition Model For Viscoelastic Liquidsmentioning
confidence: 99%
“…The volume of fracturing water injected into each well is typically more than 50,000 m 3 . However, only 5–50% of the injected fracturing water returns to the surface after the fracturing process due to leak-off and capillary imbibition from the fracture face into the shale matrix. Recent experimental observations suggest that because shale formation exhibits ultra-low initial water saturation and high clay content, the imbibed water and clay swelling may block the gas transport pathway in the shale matrix (Figure ), thus preventing migration of shale gas to the fracture. The impact of retained fracturing water on shale gas transport (gas diffusivity and permeability) has been evaluated in many published literature studies. Chen et al (2022) reported 57% reduction in diffusivity when Longmaxi organic-rich shale was exposed to water for 48 h. A similar blockage effect was also documented in many other organic-rich tight rocks dominated by nanopore systems. The negative effect on matrix permeability is also observed to be a drastic reduction when exposed to water.…”
Section: Introductionmentioning
confidence: 99%
“…The network can be either extracted from pore space for real applications or generated artificially for mechanism study. In recent years, exciting developments have been made in algorithms for PNMs (Chen et al., 2021; Mehmani & Xu, 2022; Qin et al., 2022; Xie et al., 2017), yet, the efforts paid to network extraction from real pore space, which is the basis of pore network modeling for real applications, are still not enough. In the early studies of PNMs, regular networks (Chatzis & Dullien, 1977; Jerauld & Salter, 1990) were mostly adopted.…”
Section: Introductionmentioning
confidence: 99%